The Men and the Boys, Twenty Years On: Revisiting Raewyn Connell's Pivotal Text. Issue 2 (1st December 2020) - Cann, Victoria; Madrid, Sebastián; Ratele, Kopano; Tarrant, Anna; Ward, Michael R.M.; Connell, Raewyn
Abstract : It is twenty years since the publication of Raewyn Connell's highly influential text The Men and the Boys . This book, building on feminist and pro-feminist perspectives of gender formation, was written over a ten-year period from the late 1980s to the late 1990s. It was published five years after the release of the groundbreaking text Masculinities (1995) and tackled multiple issues concerning boys and men. While providing an important platform and summary of where the research from the social science and humanities on men and masculinities stood in the year 2000, the book also contained a theoretical framework for understanding men and masculinities as part of gender relations. Importantly, the future direction of the field was outlined, and suggestions were made as to likely future agendas. These subjects included investigating the implications of globalization and its different characteristics on gender formation, the role of men's bodies, the impact of the media and culture in men's lives, sexuality, education, health, politics, change, violence, and peace. In recent years, questions about the lives and experiences of men and boys continue to raise remarkable media interest, public concern, and controversy on a global scale. Global changes in practices of knowledge have ensured that across the humanities and social sciences, research in the field of masculinities (of all ages) has continued to flourish and expand.